2005
DOI: 10.1111/j.1365-2303.2004.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of liquid‐based cytology associated with curettage in the investigation of endometrial lesions from postmenopausal women

Abstract: Endometrial sampling is complementary to D&C for the diagnosis of endometrial lesions and it is necessary for it to be performed before D&C and/or hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 20 publications
5
31
0
2
Order By: Relevance
“…The main advantages of this procedure are the reduction in confounding factors, the distribution of cells on a thin layer and the possibility to obtain more slides from the same sample. The two LBP technologies currently in use include ThinPrep (Hologic Inc., Bedford, Mass., USA) and SurePath (BD Diagnostics, Burlington, N.C., USA) and several groups have reported their experience either by using ThinPrep [10,11,14,15] or SurePath [8,9,12,13] methods. There are subtle differences between ThinPrep and SurePath preparations which reflect different sampling devices, collection media and processing techniques [20,21,22,23].…”
Section: Processing Of Endometrial Lbp Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main advantages of this procedure are the reduction in confounding factors, the distribution of cells on a thin layer and the possibility to obtain more slides from the same sample. The two LBP technologies currently in use include ThinPrep (Hologic Inc., Bedford, Mass., USA) and SurePath (BD Diagnostics, Burlington, N.C., USA) and several groups have reported their experience either by using ThinPrep [10,11,14,15] or SurePath [8,9,12,13] methods. There are subtle differences between ThinPrep and SurePath preparations which reflect different sampling devices, collection media and processing techniques [20,21,22,23].…”
Section: Processing Of Endometrial Lbp Methodsmentioning
confidence: 99%
“…Garcia et al [23] noted that LBP endometrial cytology has good specificity and positive predictive value for the detection of endometrial abnormalities and has a lower rate of unsatisfactory diagnoses compared to biopsy. It has been reported [10,11] that examination of just one slide provides sufficient material for cytological evaluation of an endometrial sample. Therefore, although the preparation area of LBP is smaller than conventional methods, LBP contains cells of adequate quantity and quality for a possible diagnosis [8,9].…”
Section: Cellular Findings In Lbp Methods Using Cytoarchitectural Featmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid-based cytology, because of its capacity to reduce obscuring factors such as blood and inflammatory cells as well as providing a thin-layer sample, represents an opportunity to reevaluate endometrial cytology. An increasing interest in endometrial cytology is demonstrated by a number of articles reporting favorable results in terms of diagnostic accuracy [16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…In endometrial disease, cytology is a simple, painless, inexpensive and accurate way to obtain material for cancer detection and for morphological diagnosis [12]. It can also be used to study preventive and predictive markers, including PTEN [13].…”
Section: Introductionmentioning
confidence: 99%